Does race influence health-related quality of life outcomes in older patients who undergo advanced cardiac surgical therapies? - Jerian Dixon-Evans, PhD, MHA, CCRP; Tingqing Wu, MPH; Adin-Cristian Andrei, PhD; Shondra Clay, PhD; Kathryn Mazurek, PhD, MPH; Kathleen L. Grady, PhD, RN, MS (JHLT Open)
Background: Racial minorities are disproportionately affected by heart failure (HF). We aimed to determine whether (1) older patients (60-80 years) with HF who underwent long-term mechanical circulatory support (MCS, i.e., destination therapy), compared to patients who underwent heart transplantation (HT), with (HT MCS) or without (HT non-MCS) pretransplant MCS, experienced noninferior change in overall health-related quality of life (HRQOL) by race (White vs racial minorities) from baseline to 1-year postoperatively and (2) race was a risk factor associated with overall HRQOL at 1-year postoperatively. Methods: Patients were recruited from 13 US medical centers (n = 305). Of the 305 patients who underwent surgery, 107 long-term MCS, 56 HT MCS, and 87 HT non-MCS had data through 1-year follow-up. Analyses included noninferiority (NI) testing using the Kansas City Cardiomyopathy-12 Questionnaire overall summary score (KCCQ-12 OSS, score range = 1[worst]-100[best] HRQOL) at baseline and 3-, 6-, and 12-months follow-up and multivariable linear regression. Results: The cohort's average age was 66 years, 78% were male, and 84% were White. The long-term MCS racial minority group did not demonstrate NI compared to the HT MCS and HT non-MCS racial minority groups, and the White long-term MCS group did not demonstrate NI compared to the White HT MCS and HT non-MCS groups. Sex (male) and surgical strategies (HT MCS and HT non-MCS) were positively associated with the KCCQ-12 OSS, whereas the number of postoperative adverse events was negatively associated. Conclusions: Patients experienced improved HRQOL after surgery, regardless of race; demographic and clinical factors were associated with HRQOL.